Perilaku ‘Food Approach’ Pada Anak Prasekolah : Studi Kualitatif - Herni Dwi Herawati; Indria Laksmi Gamayanti; A Fahmi Arif Tsani; I Made Alit Gunawan (Poltekkes Kemenkes Yogyakarta, 2016)
Background : the prevalence of obesity in preschool children was increasing. Food approach behavior was the cause of obesity in children. Objective :to describe food approach behavior in preschool children who have obese and normal nutritional status. Method:this research was qualitatif study. Sampling was done by purposive sampling in mothers who had preschool children aged 3-5 years, consist of two groups; mothers who had obese children (Zscore weight/height > 2 SD), and mothers who had normal nutritional status children. The data colllection was done in-depth interview. Results:in children who were obese more describing overeating, enjoyment of food and desire to drink than in children who were normal nutritional status. Conclusion:obese children tend to describe food approach behavior. Keyword:food approach, preschool children, qualitative study